Cytotoxic properties of anthraquinones (nordamnacanthal and damnacanthal) from roots of Morinda elliptica - Saiful Yazan, Latifah (2003)
The study on the cytotoxic properties of nordamnacanthal and damnacanthal, the anthraquinones isolated from the roots of Morinda elliptica (family Rubiaceae) were carried out on several cancerous cell lines including CEM-SS (T-lymphoblastic leukaemia), KU812F (chronic myelogeneous leukaemia), WEHI-3 (leukaemia), HT29 (colon cancer) and HeLa (cervical adenocarcinoma). The degree of cytotoxicity of the compounds were defined by their abilities at certain concentration to cause 50% reduction in cell number relative to the untreated sample, and termed as IC50 value. CEM-SS was observed to be the most sensitive cell line towards nordamnacanthal and damnacanthal with the ICso values of 1.7 µg/ml and 10 µg/ml, respectively, as detected by the colorimetric tetrazolium-based assay (MTT). The compounds also showed cytotoxicity to the non-cancerous cell lines such as HF19 (lung fibroblast), human peripheral blood mononuclear (PBMC), 3T3 (mouse embryo) and Vero (monkey kidney fibroblast) but at very high concentrations (>30 µg/ml). Themicroscopic analysis on the treated CEM-SS cells including light m icroscopy without staining or following staining with haematology polychrome, Giemsa and Wright's stains, fluorescence microscopy following staining with acridine orange and propidium iodide, and scanning and transmission electron microscopy showed that these compounds induced two types of cell death, apoptosis and necrosis. At the molecular level, these compounds caused intemucleosomal DNA cleavage producing multiple of 180-200 bp fragments that are visible as a "ladder" on the agarose gel. The DNA fragmentation has been found to be due the activation of the Mg2+/Ca2+-dependent endonuclease. The induction of apoptosis by nordamnacanthal was different from the one induced by damnacanthal in a way that it occurs independently of ongoing transcription process. Nevertheless, in both cases, the process of dephosphorylation of protein phosphates 1 and 2A, the ongoing protein synthesis and the elevations of the cytosolic Ca2+ concentration were not needed for apoptosis to take place. Nordamnacanthal and damnacanthal at their ICso values showed different mechanism by which they exert their cytotoxic effects. Nordamnacanthal was found to have cytotoxic effect by inducing apoptosis in CEMSS cells. Damnacanthal, on the other hand, showed cytostatic effect by causing arrest at the GO/G1 phase of the cell cycle. Nordamnacanthal was also found to reduce the expression of bcl-2, thus stimulating the process of apoptosis in CEM-SS cells.